MENINGKATKAN HASIL BELAJAR PKN MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE JIGSAW SISWA KELAS IV SD NEGERI 012 SILIKUAN HULU KECAMATAN UKUI - Sudahana ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by lack of civics student learning outcomes. Low studentlearning outcomes is caused by: (a) the teaching methods teachers are passive andmonotonous; and (b) the students were cool to mess around when lessons. This study aims toimprove student learning outcomes. This research is a class act, performed in SD Negeri 012Silikuan Hulu. The data used in this study is the activity data of teachers and students as wellas civics student learning outcomes. Based on the results of the study revealed that theactivities of teachers and students and the learning outcomes of students has increased. Thisis evidenced by the acquisition: the preliminary data the number of students who completed is10 students, an increase in the first cycle by the number of students increased to 15 studentsand 17 students in the second cycle. Teacher activity also increased in the first cycle ofmeeting 1 percentage teacher activity by 47%, in the first cycle of meeting 2 increased withthe percentage of 56%. In the second cycle 1 meeting increased to 68% and the second cycle2 meeting increased to 73%. Student activity also increased in the first cycle 1 meeting apercentage of student activity by 50%, in the first cycle of meeting 2 increased with thepercentage of 57%. In the second cycle 1 meeting increased to 65% and the second cycle 2meeting increased to 82%.